Emotional intelligence role: Relationship between role conflict and role ambiguity on external auditor performance - Muslim, Muslim (Advances in Managerial Auditing Research, 2023)
Purpose: This study uses emotional intelligence as a moderating variable between the influence of role conflict and unclear role on external auditors' performance in Makassar. Research Design and Methodology: The study population was 47 auditors at 9 Public Accounting Firms (KAP) in Makassar. The selection of research samples using a saturated sampling method or census. The data of this study were analyzed using multiple linear regression methods with the help of Smart PLS 3.0 software. Findings and Discussion This study found that role conflict variables and role ambiguity negatively and significantly affected auditor performance. Role conflict positively and substantially affects auditor performance with moderated emotional intelligence. Unclear role does not considerably influence auditor performance with moderate emotional intelligence. Implications: Emotional intelligence controls, such as empathy for clients, exist. Of course, by controlling emotional intelligence, role conflict, and role ambiguity can be prevented and reduced, increasing the auditor's performance.